The gap between the conditional wage distributions of incumbents and the newly hired employees: Decomposition and uniform ordering - Esfandiar Maasoumi; M. Melinda Pitts; Ke Wu (Federal Reserve Bank of Atlanta, 2014)
We examine the cardinal gap between wage distributions of the incumbents and newly hired workers based on entropic distances that are well-defined welfare theoretic measures. Decomposition of several effects is achieved by identifying several counterfactual distributions of different groups. These go beyond the usual Oaxaca-Blinder decompositions at the (linear) conditional means. Much like quantiles, these entropic distances are well defined inferential objects and functions whose statistical properties have recently been developed. Going beyond these strong rankings and distances, we consider weak uniform ranking of these wage outcomes based on statistical tests for stochastic dominance. We focus the empirical analysis on employees with at least 35 hours of work in the 1996 - 2012 monthly Current Population Survey. Among other findings, we find incumbent workers enjoy a better distribution of wages, but the attribution of the gap to wage inequality and human capital characteristics varies between quantiles. For instance, highly paid new workers are mainly due to human capital components and, in some years, even better wage structure.
Keywords: I31; C43; 330; wage gap; metric entropy distance; stochastic dominance; wage distributions; counterfactual analysis; human capital; inequality; labor markets